2003
DOI: 10.2514/2.6802
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Individual Cotton Fibers via Light-Scattering Experiments

Abstract: A detailed experimental/theoretical study is conducted to explore the fundamental nature of individual cotton bers via light-scattering experiments. For this purpose, a new precision nephelometer is built and calibrated with quartz bers. In the experiments, iris opening (viewing angle) and scanning range and rate were determined to be the key parameters for precision measurements. The experimental results are compared against the theoretical predictions based on a nite element model. It is shown that the scatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…12 Aslan et al obtained the scattering rule for single cotton fibers using the finite element method (FEM). 13 Furthermore, the scattering theory of an infinitely long cylinder has been widely researched. 14 It can be concluded that scattered light is confined in a cone, which is oriented around the cylinder axis.…”
Section: Materials and Spectral Informationmentioning
confidence: 99%
“…12 Aslan et al obtained the scattering rule for single cotton fibers using the finite element method (FEM). 13 Furthermore, the scattering theory of an infinitely long cylinder has been widely researched. 14 It can be concluded that scattered light is confined in a cone, which is oriented around the cylinder axis.…”
Section: Materials and Spectral Informationmentioning
confidence: 99%
“…Polarized light scattering‐based techniques (PLST) have been successfully used to characterize a number of systems such as colloidal particle suspensions, milk, cotton fibres, living epithelial cells, and nanoscale air bubbles based on their multiple scattering behaviours. However, only primary studies on applying polarized light scattering techniques on foams have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Light scattering and propagation in textile material, e.g., transflectance, single scattering, and backscattering, have been employed experimentally on mass measurement [1], quality examination [2,3], area density determination [4], and structural analysis [5]. In the abovementioned applications, light scattering and propagation in textile material are favorable; they are unfavorable to our study on the detection of impurities hidden in textile material (such as cotton fiber assemblies) with polarized incident light.…”
Section: Introductionmentioning
confidence: 99%